(untitled) (Global Journal of Human-Social Science, 2017)
Thanks to globalization mass media especially news media is controlled by the largest multinational companies of the world The multinational form of the media has started influencing every sector of life of the people in the world because the media as a social institution is working as an intermediary in the practices of socio-economic and politico-cultural norms it is building both the individual and universal identity and is designing the road map for our daily life However like other corporate organization the media is also running behind the profits News like other profitable goods is becoming the way to profits of the multinational companies Though the newspaper is considered the mirror of the society fourth pillar of the country the consciousness of the nation etc it is criticized by the scholars The multinational companies have been using media as a way to profit instead of the way for social change In this study the evolution and nature of the media under the corporate organization in Bangladesh has been discussed and analyzed critically The objective of the research is to investigate how the capitalism known as the basic structure of the media media economy is influencing the superstructure of the media contents news and advertisement Through content analysis of four national dailies and in-depth interview of media experts the article illustrates how the corporate organization is influencing the news The present study also depicts investigates the corporate news organization and the ownership of the media in Bangladesh with mentioning the history of the corporate media organization in the Western countries In this perspective the contemporary practices of the journalism and its nature in Bangladesh are also elaborated here